Self- and other-dehumanization processes in health-related contexts: a critical review of the literature - Diniz, E.; Bernardes, S. F.; Castro, P. (Review of General Psychology, 2019)
Dehumanization is an everyday, pervasive phenomenon in health contexts. Given its detrimental consequences to health care, much research has been dedicated to understanding and promoting the humanization of health services. However, health care service research has neglected the sociopsychological processes involved in the dehumanization of self and others, in formal but also informal health-related contexts. Drawing upon sociopsychological models of dehumanization, this article will bridge this gap by presenting a critical review of studies on everyday meaning-making and person perception processes of dehumanization in health-related contexts. A database search was conducted in PsycINFO, Web of Science, Scopus, and PubMed, using a combination of keywords on dehumanization and health/illness/body; 3,229 references were screened; 95 full texts were assessed for eligibility; 59 studies were included. Most studies focused on informal contexts, reflecting a decontextualized and one-sided view of dehumanization (i.e., not integrating actors’ and victims’ perspectives). Despite the dominant focus on self-dehumanization, emerging perspectives uncover the role of processes that deny human uniqueness to others, and their individual determinants and consequences for mental health. A few studies bring to light the functions of a variety of dehumanizing body metaphors on self- and other-dehumanization. These trends in the literature leave several gaps, which are here critically analyzed to inform future research.